Pathogenesis of congenital alkalosis with diarrhea. Implications for the physiology of normal ileal electrolyte absorption and secretion - Bieberdorf, F A; Gorden, P; Fordtran, J S (The Journal of clinical investigation, 1972)
Using a triple-lumen constant perfusion system, we have studied ileal electrolyte transport in a patient with congenital alkalosis with diarrhea and made the following observations. First, chloride cannot be transported against electrochemical gradients, but can be readily absorbed or secreted down electrochemical gradients. Second, chloride secretion down an electrochemical gradient can be increased by raising lumen bicarbonate concentration. Third, sodium absorption does occur against electrochemical gradients and is associated with hydrogen ion secretion. Fourth, electrical potential difference (PD) between lumen and blood is near zero when lumen sodium concentration is 140 mEq/liter. Fifth, a normal sodium diffusion potential is present. Sixth, potassium is transported passively in response to electrochemical gradients. The ileal electrolyte transport disorder of congenital alkalosis with diarrhea can be simulated exactly in normal subjects perfused with a solution in which chloride is replaced with poorly absorbable sulfate and phosphate. These results can be explained by postulating a single defect in the double ion exchange model (sodium-hydrogen, chloride-bicarbonate) previously proposed for normal ileal transport: i.e., normal sodium-hydrogen exchange, but a chloride-bicarbonate exchange that is incapable of transporting chloride against an electrochemical gradient, yet continues to transport anions passively. In contrast, the results appear incompatible with the concept of ileal electrogenic sodium transport.